DNA fingerprinting to distinguish the coconut type, San Ramon - C.K. Bandaranayake; W.B.S. Fernando; A. Fernando; N. Herath (International Coconut Community, 2005)
San Ramon, an introduced type of coconut from Philippines, has long been in Sri Lanka. San Ramon has the advantage of producing high copra, high oil, and high-quality timber and also seemed to be less variable for bunch characters. In addition, it is a type of coconut having an ability to withstand long droughts and also coconut mites. Due to these outstanding beneficial characters, San Ramon has been used as a parent for effecting various crosses to transmit the drought tolerance nature and high copra outturn, to the offspring. The physical structure of San Ramon palms is much comparable to tall type coconuts though there are some specific characters predominantly seen in favourable environments. On top of these circumstances, it is not easy to separate San Ramon from other Talls and virtually impossible to distinguish pure San Ramon from San Ramon crosses by means of only morphological markers. Therefore, a molecular finger-printing method was attempted to distinguish pure San Ramon using already developed 10 coconut SSR primers. The results indicate the possibility of distinguishing pure San Ramon from its crosses with the help of 2 coconut SSR primers, CNZ6 and CNZ44.